On Genus Amorphophallus Blume ex Decne (Araceae) in Cuba - Roeris González-Sivilla (Universidad de Camagüey Ignacio Agramonte Loynaz, 2021)
Context: The presence in several Cuban cities of Amorphophallus Blume ex Decne (Araceae), which has been poorly and unelaborately published in the scientific literature, encouraged researchers to conduct a systematic, phytogeographic, and ethnobotanical study of this plant.